Effectiveness of Hybrid Learning Model Against Student HOTS in Learning Microbiology at IKIP Budi Utomo - Purwaning Budi Lestari; Tri Asih Wahyu Hartati; Budijanto Budijanto (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2022)
High Order Thinking skill (HOTS) students very needed during the COVID-19 pandemic. Objective study this is to determine the effectiveness of the hybrid learning model to High Tinking Order Skill (HOTS) students at the Microbiology MK at IKIP Budi Utomo. Method research used is quasi-experimental. The research subjects are IKIP Budi Utomo students who are currently studying go through eye studying microbiology in the even semester 2020/2021. Technical data analysis performed for know the distribution of research data with the n -normality test using the SPSS 16 program. The differences between the pretest and posttest values of the subject groups were tested. Differences in posttest scores, HOTS scores were analyzed using the General Linear Model (GLM) Multivariate SPSS 16 program. Research results show the average HOTS with hybrid learning (72.2727) is more tall compared to learning conventional (54.2857). Further test results show there is significant difference between the hybrid learning model and the conventional model against student HOTS. In conclusion, the hybrid learning model is effective in improve student HOTS in learning microbiology.